Answer:
Option A) [tex](-x^2 - 2x + 4)-(x^2 + 2x +1)= -2x^2-4x +3[/tex] is modeled by the algebra tiles
Step-by-step explanation:
Given [tex](-x^2 - 2x + 4)-(x^2 + 2x +1)= -2x^2-4x + 3[/tex]
To verify that the given sum or difference is modeled by the algebra tiles
Now applying the algebraic sum operations we get
[tex](-x^2 - 2x + 4)-(x^2 + 2x +1)=-x^2 - 2x + 4 - x^2 - 2x -1[/tex]
[tex]= -2x^2-4x + 3[/tex] ( using algebraic sum operations )
Therefore [tex](-x^2 - 2x + 4)-(x^2 + 2x +1)=-2x^2-4x + 3[/tex]
Option A) [tex](-x^2 - 2x + 4)-(x^2 + 2x +1)=-2x^2-4x + 3[/tex] is modeled by the algebra tiles